Eldorado or Fortress? Migration in Southern Europe
XIV, 351 p. 5 illus.
Keywords: As Europe struggles to control immigration, the EU's southern flank is perceived as the weak flank of 'Fortress Europe'. This book examines the many facets of Southern Europe's new immigration: the diverse roles played by immigrants in the labour market, issues of social exclusion and wider strategic concerns of security and geopolitics.